Position and Role of sharia Banks on Murabahah Contract Implementation - Muh. Fudhail Rahman; Aida Humaira (Jurnal Madania)
The legality and validity of sharia banks still somehow lead to some problems, including a negative view of the use of murâbahah contract at the level of practice in the field. Is it true that the application of the sale and purchase agreement of sharia banks, in this case the contract of murâbahah, salam and istisnâ’, is essentially a sale and purchase process? This is a critical question in this research. This is a critical question in this research. Such a miserable view not only emerged in the country, but also voiced in several other Muslim countries. This type of research is a qualitative descriptive method with content analysis of qualitative / inductive data. Data sources are the results of interviews with Sharia Commercial Banks (BUS) BNI, Sharia Business Units (UUS) Permata Syariah and Sharia People’s Credit Banks (BPRS) Al-Salam. This research shows that sharia banks which are still dominant in using murâbahah contracts are not appropriate. Judging from the aspect of sharia maqâsid, the position of shariah banks is basically outwardly not acting as a provider of goods. Sharia banks do not have a stock of goods as a meaning of the use of contracts based on exchange or sale and purchase transactions. In fact, the position and position of a sharia bank is essentially only as an institution mediating financial service providers and not sellers. However, from the perspective of jurisprudence the practice of murâbahah in Sharia Financial Institutions (LKS) has fulfilled the pillars and conditions, but in the absence of stock of goods, the sale and purchase transactions of sharia banks seem still as al-makhârij al-shar’î (sharia solutions).